Global insight into a complex-structured heliosphere based on the local multi-point analysis - Pal, Sanchita; Balmaceda, Laura; Weiss, Andreas J.; Nieves-Chinchilla, Teresa; Carcaboso, Fernando; Kilpua, Emilia; Möstl, Christian (Frontiers in Astronomy and Space Sciences, 2023)
From January 29 to February 7, 2022, the heliosphere was structured with large-scale interacting substructures that appeared with significant dissimilarities at distant observations separated longitudinally by $\sim 34 ^°$. Probing the complexity of the structured heliosphere with multi-point in situ and imaging observations by using a fleet of spacecraft has revealed many unknown facts on the dynamics of large-scale structures in the heliosphere. In this paper, we investigate a complex structured heliosphere by analyzing the Sun, solar corona, and solar wind with remote and in situ observations aided by heliospheric modeling. We identified multiple flux ropes (FRs) associated with large expulsions of magnetized plasma -- coronal mass ejections (CMEs) -- from the same solar source in the three-day interval, an interplanetary wave shock, and sheath in front of the FRs. In situ observations displayed a stream interaction region behind FRs formed due to the overtaking of different-speed solar wind. This high-speed stream originated from a coronal hole located southeast of the CME solar source. We find evidence of merging FRs, FR deflection due to the presence of the nearby coronal hole, and FR's unalike structural appearance at distant multi-point observations obtained at 1 au. This complex structured heliosphere resulted in multiple G1-class geomagnetic storms when interacting with the Earth's magnetosphere. Thus, the study focuses on the reconstruction of the structured heliosphere based on observations and modeling. It highlights the importance of multi-point observations in understanding the global configuration and disparity in the local nature of a structured heliosphere.